Potency of Super Red Dragon Fruit Flesh Extract (Hylocereus costaricencis) in Herbal Lipstick as Colorant, Antioxidant and Antibacterial - Anjarsari, Lusiana Dian; Aditiyarini, Dwi; Guntoro (SCISCITATIO, 2020)
Lipstick is one kind of cosmetics which is used as lips colorant to increase self-confidence. Nowadays, lipsticks from natural source is popular to reduce the negative impact of chemical compound or synthetics colorant in lipstick intensively for health. Super red dragon fruit is one kind of natural ingredients which can be used as colorant for lipstick. Moreover, this fruit is rich of antioxidant and antibacterial component that is good for skin health. In this research, extract of super red dragon fruit flesh was added in the lipstick during preparation with variation of concentration 0, 10, 20, 30 and 40%. Antioxidant analysis resulted the IC50 value in 81.55% indicating the strong antioxidant properties. Furthermore, the concentration of dragon fruit extract 40% was able to inhibit the growth of Staphylococcus aureus bacteria.